De Concept à l'objet: la fabrication d'une sculpture - Bouchard, René; Genest, Bernard (Ethnologies, 1980)
AbstractAfter a brief introduction to the artist, a sculptor of animais from Portneuf County, Quebec, the authors describe in detail the different stages in the making of a little wooden horse, from its conception to the application of colour. The description relies on a sériés of photographs capturing each phase of construction and a tape-recorded interview makes available the artist's thoughts on his work.